SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN DI MI MUHAMMADIYAH BANJAR AGUNG OKU TIMUR: Volume 1, Nomor 1 (2024) - Sendy Adi Saputra (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
Academic supervision carried out by the head of MI Muhammadiyah Banjar Agung OKU Timur is an effort to improve the quality of learning through coaching and guidance to teachers in planning learning, implementing the learning process, and evaluating student learning outcomes in order to achieve predetermined goals. This research was conducted with the aim of; Describe the planning for academic supervision carried out by the head of MI Muhammadiyah Banjar Agung OKU Timur. This research uses a descriptive qualitative approach, namely the researcher only describes, analyzes phenomena, events and activities carried out in relation to academic supervision carried out by the head of MI Muhammadiyah Banjar Agung OKU Timur with data collection techniques through: (1) Observation (2) Interview In-depth, and (3) Documentation Study. The selection of research informants used purposive techniques combined with Snowball Sampling. The data collected through the three techniques was then checked for validity by triangulation. Then analyzed by: (1) data reduction, (2) data presentation and (3) drawing conclusions. Based on the research results, the following findings can be concluded: (1) The academic supervision program for the head of MI Muhammadiyah Banjar Agung OKU Timur was prepared based on the results of supervision analysis and monitoring of previous learning processes; The principal’s academic supervision program is prepared at the beginning of the school year, by first identifying problems, determining objectives and determining the time for implementation, involving the deputy head of curriculum, deputy head of quality assurance, and teachers; and carried out systematically, (2) The strategy for implementing the principal’s academic supervision includes: supervising learning tools, supervision using class visit techniques, and observing teacher activities in class, and implementing follow-up on the results of academic supervision in the form of personal and group coaching. (3) The implications of the principal’s academic supervision are: (a) Increased teacher ability in compiling learning tools (b) Increased teacher ability in carrying out the learning process, (c) Increased teacher ability in evaluating student learning outcomes.